2001
DOI: 10.1093/geront/41.3.322
|View full text |Cite
|
Sign up to set email alerts
|

The Positively Aging® Teaching Materials Improve Middle School Students' Images of Older People

Abstract: This controlled study demonstrated that use of the Positively Aging teaching materials and activities moved middle school students toward a more positive view of elders. Interdisciplinary teaching materials based on geriatrics and gerontology can be successfully developed and tested in public school systems to affect attitudes about aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 13 publications
0
11
0
1
Order By: Relevance
“…A less commonly used strategy relies on sketches of elders drawn by respondents (Barrett & Cantwell, 2007;Falchikov, 1990;Lichtenstein, Pruski, Marshall, Blalock, Murphy, Plaetke, et al, 2001;Lichtenstein, Pruski, Marshall, Blalock, Liu, Plaetke, et al, 2005;Weber, Cooper, & Hesser, 1996). Features of sketches that have been analyzed include facial expressions and the depiction of physical aids and wrinkles.…”
Section: Views Of Eldersmentioning
confidence: 99%
“…A less commonly used strategy relies on sketches of elders drawn by respondents (Barrett & Cantwell, 2007;Falchikov, 1990;Lichtenstein, Pruski, Marshall, Blalock, Murphy, Plaetke, et al, 2001;Lichtenstein, Pruski, Marshall, Blalock, Liu, Plaetke, et al, 2005;Weber, Cooper, & Hesser, 1996). Features of sketches that have been analyzed include facial expressions and the depiction of physical aids and wrinkles.…”
Section: Views Of Eldersmentioning
confidence: 99%
“…The lack of association in adolescent minds between health and future outcomes provides opportunities for health promotion education with a lifecourse perspective. A controlled study of TEI Program materials demonstrated that their use could positively impact student images of elders (21). To improve health science literacy will require similar educational research to test new curricula in schools and measure what works.…”
Section: Lifecourse View Of Healthmentioning
confidence: 99%
“…Young adolescents are at a developmental stage where they are especially receptive to information about themselves and are more independent in their decision-making (6,21). A time of change, physically, socially, emotionally, and intellectually, adolescence is also a time of growth, learning, and exploration.…”
Section: The Tei Program's Rationale For Working With Middle Schoolsmentioning
confidence: 99%
“…Aging education can help to overcome ageism and counteract societal myths and misinformation about aging (Palmore, 2004). It has the potential to reverse or prevent ageist attitudes, promote positive attitudes about aging, and help people to see the potentials of aging (Blunk & Williams, 1997, Chowdhary, 2002Fecht, 1990;Kamenir, 1983;Laney, Wimsatt, Moseley, & Laney, 1999;Langer, 1999;Lichtenstein et al, 1999;Lichtenstein et al, 2001;Lucchino, Lane, & Ferguson, 1997;McGuire, 1993a;McGuire, 1994;Palmore, 2004;Southall, 1984). ''If we teach children that growing old is a natural part of life, and raise them to appreciate and value the contributions of older people to their world, ageist stereotypes and fears of growing old will become obsolete'' (Butler, 1999, p. v).…”
Section: Why Teach About Aging?mentioning
confidence: 99%